Prescribed Anti-Racism? Historic and Contemporary Challenges to a Global Memory Imperative (KULT_online, 2020)
This excellent book on Holocaust Memory and Racism challenges the widespread assumption that learning about the Holocaust automatically makes us better people. In fifteen contributions, the authors assembled in this volume look at various national case studies that demonstrate how, from the early post-war period up until today, it has been all too common to strongly oppose Nazism and its racist policies but at the same time keep racism as an unquestioned organizing principle of one’s own society. To approach the universalization of the Holocaust that turned it into the ultimate “symbol of racism and injustice” (p.5) the publication focusses on societies that have not directly been affected by Nazism. Thereby the different chapters discuss issues of prevailing racism as well as anti-racist engagements and take into consideration the value of empathetic connections between victims of the Nazis and victims of Colonialism. A highly recommended read.